Technology, Policy, and Inclusion An Intersection of Ideas for Public Policy - Prakash, Anjal; Jain, Aarushi; Singh, Puran; Sarkar, Avik (Innovations, Practice and the Future of Public Policy in India, 2024)
Technology, Policy, and Inclusion looks at the intersections between public policy and technology in India. It explores the barriers in instituting effective governance and development and examines how these can be mitigated through technological interventions in developing countries. Increased digitisation of the economy has added to the development challenges in India and issues such as exclusion and social inequality. This volume stresses the need for governments to leverage technology to bring more vulnerable and marginalised groups into the fold of financial and social inclusion. It also focuses on the importance of regulation for a responsible integration of technologies and minimising risks. The book includes examples and case studies from different areas including management of the COVID-19 pandemic through digital means, real estate digital infrastructure, digital census, e-markets for farmers, and government interventions that use technology to deliver financial services in remote areas of the country. It also outlines various solutions for fostering equity and socio-economic development. Part of the Innovations, Practice and the Future of Public Policy in India series, this volume will be of interest to students and researchers of public policy, political science, development studies, and sociology as well as policy professionals and technocrats. This book is freely available as a downloadable Open Access PDF at http://www.taylorfrancis.com under a Creative Commons (CC-BY-NC-ND) 4.0 license.